2016
DOI: 10.1097/pts.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Information Transfer at Hospital Discharge: A Systematic Review

Abstract: Delayed or insufficient transfer of discharge information between hospital-based providers and PCPs remains common. Creation of electronic discharge summaries seems to improve timeliness and availability but does not consistently improve quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 38 publications
3
70
1
1
Order By: Relevance
“…Between 35% and 59% of MRH was preventable in the included studies, and this finding builds on a previous systematic review of MRH in the community (not after discharge) in all age groups which reported that 11% to 27.5% as preventable . Given the high risk around hospital discharge of medication discrepancies, poor communication of medication changes and possible adverse effects, and deficiencies in information transfer to primary care, the higher proportion of preventable MRH that we found is not a surprise.…”
Section: Discussionsupporting
confidence: 80%
“…Between 35% and 59% of MRH was preventable in the included studies, and this finding builds on a previous systematic review of MRH in the community (not after discharge) in all age groups which reported that 11% to 27.5% as preventable . Given the high risk around hospital discharge of medication discrepancies, poor communication of medication changes and possible adverse effects, and deficiencies in information transfer to primary care, the higher proportion of preventable MRH that we found is not a surprise.…”
Section: Discussionsupporting
confidence: 80%
“…While such tools may be specifically useful for the German rehabilitation system, the barrier of timely transmission of relevant findings and the translation of findings from one specific setting or expert group to another is well known in health services research. Delayed and/or insufficient transfer of information are especially common in the discharge communication between hospital-based to outpatient health care providers (Kripalani et al 2007a, b; Kattel et al 2016). It is therefore likely that similar solutions may be useful in the rehabilitation systems in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that similar solutions may be useful in the rehabilitation systems in other countries. Although not specifically focused on rehabilitation, the international literature supports structured formats and technology solutions as well as standardized language in order to improve availability, completeness, timeliness, and quality of discharge information from hospitals to out-patient health care providers (Kripalani et al 2007a, b; Arora et al 2009; Hesselink et al 2012; Kattel et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In stroke/TIA, patients are treated in hospital and general practitioners (GPs) often depend on receiving discharge summaries. However, the transfer of information from hospitals to GPs may be suboptimal . In a previous publication, we introduced the concept of diagnosis recording , a potential marker of physician awareness of a clinical condition in patients transitioning from hospitals to primary care .…”
Section: Introductionmentioning
confidence: 99%